Quickly making the correct choice. (August 2015) - Brenner, Eli; Smeets, Jeroen B.J.
Highlights: People must have reasonable estimates of their own ability given the instantaneous circumstances. Abstract: In daily life, unconscious choices guide many of our on-going actions. Such choices need to be made quickly, because the options change as the action progresses. We confirmed that people make reasonable choices when they have to quickly decide between two alternatives, and studied the basis of such decisions. The task was to tap with their finger on as many targets as possible within 2 min. A new target appeared after every tap, sometimes accompanied by a second target that was easier to hit. When there was only one target, subjects had to find the right balance between speed and accuracy. When there were two targets, they also had to choose between them. We examined to what extent subjects switched to the target that was easier to hit when it appeared some time after the original one. Subjects generally switched to the easier target whenever doing so would help them hit more targets within the 2-min session. This was so, irrespective of whether the different delays were presented in separate sessions or were interleaved within one session. Whether or not they switched did not depend on how successful they were at hitting the targets on earlier attempts, but it did depend on the position of the finger at the moment that the easy target appeared. We conclude that people have continuous access to reasonable estimates of how long various movement options would take and of how precise the endpoints are likely to be, given the instantaneous circumstances.